2015
DOI: 10.1371/journal.pone.0117123
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D₃ Supplementation in Batswana Children and Adults with HIV: A Pilot Double Blind Randomized Controlled Trial

Abstract: ObjectivesSince vitamin D insufficiency is common worldwide in people with HIV, we explored safety and efficacy of high dose cholecalciferol (D₃) in Botswana, and evaluated potential modifiers of serum 25 hydroxy vitamin D change (Δ25D).DesignProspective randomized double-blind 12-week pilot trial of subjects ages 5.0–50.9 years.MethodsSixty subjects randomized within five age groups to either 4000 or 7000IU per day of D₃ and evaluated for vitamin D, parathyroid hormone, HIV, safety and growth status. Efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 26 publications
4
37
1
Order By: Relevance
“…According to a recent review by Mansueto et al [ 96 ] the prevalence of vitamin D deficiency among HIV-infected individuals in both RLS and RRS varies widely across studies ranging from 25 to 93%, with an overall prevalence of 70.3 to 83.7%. Similarly, our review yielded high but similar prevalence of low vitamin D among HIV individuals regardless of ART use in both RLS [ 50 , 53 , 97 102 ] and RRS [ 61 , 103 109 ] with insufficient levels of up to 90% in Turkey [ 50 ] and the USA [ 103 ], Belgium [ 108 ], Spain [ 109 ] (Table 2 and Fig. 2 ).…”
Section: Introductionsupporting
confidence: 54%
“…According to a recent review by Mansueto et al [ 96 ] the prevalence of vitamin D deficiency among HIV-infected individuals in both RLS and RRS varies widely across studies ranging from 25 to 93%, with an overall prevalence of 70.3 to 83.7%. Similarly, our review yielded high but similar prevalence of low vitamin D among HIV individuals regardless of ART use in both RLS [ 50 , 53 , 97 102 ] and RRS [ 61 , 103 109 ] with insufficient levels of up to 90% in Turkey [ 50 ] and the USA [ 103 ], Belgium [ 108 ], Spain [ 109 ] (Table 2 and Fig. 2 ).…”
Section: Introductionsupporting
confidence: 54%
“…28,29 Moreover, participant characteristics such as age and body mass index have been reported to modify the 25(OH)D response to vitamin D supplementation. 32,33 Administration of large boluses of vitamin D has been associated with reduced efficacy for non-classical effects 20 and, in some cases, increased risk of adverse outcomes. 34 Although study-level factors are amenable to exploration via aggregate data meta-analysis of published data, potential effect modifiers operating at an individual level, such as baseline vitamin D status, can only be explored using individual participant data (IPD) meta-analysis.…”
Section: Chapter 1 Backgroundmentioning
confidence: 99%
“…Serum 25(OH)D increased slightly in the supplemented patients, and declined in those not given a supplement. Other studies among HIV patients have also shown an increase in serum 25(OH)D with vitamin D supplementation (12,13,32,33) . Longitudinal studies in HIV patients without vitamin D supplementation (34,35) have reported a decrease in serum 25(OH)D with ART initiation as observed in our study.…”
Section: Discussionmentioning
confidence: 87%